Effects of Supplementation of a Pre-workout on Power Maintenance in Lower Body and Upper Body Tasks in Women - Lane, Michael Timothy (J Funct Morphol Kinesiol, 2019)
Currently there is a lack of research into how women respond to pre-workout supplementation. The effects of supplements on exercise performance in women, specifically to power, must be performed. This study investigated the effects of supplementation on power production and maintenance during a high-intensity cycle ergometry sprint performance, vertical jump performance, and bench press performance in women. It also investigated the effects of supplementation on power production and the maintenance of upper and lower body tasks in women. A total of 23 females (22.9 ± 3.6 years, 175.6 ± 6.5 cm, 86.9 ± 15.1 kg, 19.1 ± 8.4 body fat percentage (BF%) (mean ± std. dev.)) were familiarized with the testing protocol and maximal bench press performances were attained (49.5 ± 15.4 kg). Utilizing a double-blind crossover design, subjects completed three trials of: Five countermovement vertical jumps, a high-intensity cycle sprint protocol, which consisted of 10 maximal, five second cycle ergometer sprints. Subjects performed a velocity bench press test, utilizing 80% of their predetermined one repetition maximum (1RM) for 10 sets of three repetitions for maximal speed. For 20 min prior to each trial, the subjects ingested, in a randomized order, a pre-workout supplement (Supp), placebo+150 mg caffeine (Caff), or a placebo (PL). Peak power (PP), mean power (MP), and minimum power (MNP) were recorded for each sprint. Maximal velocity from each set was also recorded. Bike sprint and bench press data were normalized to the placebo trial for analysis. Blood lactate (bLa(−)) was measured immediately prior to each testing session, within 2 min of the completion of the last cycle sprint and following the bench press test. Bike sprint and bench press testing showed no significant differences through the testing sessions, but did significantly decline over test battery (p < 0.05). Vertical jump performance and lactate levels were not significantly different. Supplementation with a pre-workout supplement or placebo with caffeine 20 min prior to participation showed no positive benefits to performance in female participants.